Setting of import tolerance for tricyclazole in rice. (18th January 2023) - ,; Bellisai, Giulia; Bernasconi, Giovanni; Brancato, Alba; Cabrera, Luis Carrasco; Castellan, Irene; Del Aguila, Monica; Ferreira, Lucien; Santonja, German Giner; Greco, Luna; Jarrah, Samira; Leuschner, Renata; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Corteva Agriscience submitted a request to the competent national authority in Italy to set an import tolerance for the active substance tricyclazole in rice. The data submitted in support of the request were found to be sufficient to derive an maximum residue level (MRL) proposal for rice. Adequate analytical methods for enforcement are available to control the residues of tricyclazole in rice at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of tricyclazole according to the reported agricultural practice is unlikely to present a risk to consumer health.